2005
DOI: 10.1111/j.1440-1746.2005.03800.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the development of hepatocellular carcinoma among patients with chronic hepatitis C who achieved a sustained virological response to interferon therapy

Abstract: Patients with CHC who had severe fibrosis, who had regularly taken moderate amounts of alcohol, or who were > or = 65 years at the start of IFN treatment should be carefully followed to detect small and controllable HCC, even after eradication of HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
79
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 40 publications
6
79
1
Order By: Relevance
“…Previous studies showed that interferon-based treatment for HCV patients could reduce the risk of hepatocellular carcinoma [17,18,19,20], but that risk factors for hepatocarcinogenesis after elimination of HCV RNA were severe fibrosis, male sex, and older age at the start of interferon treatment [20,21,22,23,24,25]. The present study based on 958 patients with HCV genotype 1 infection is the first to show that severe fibrosis and obesity are important predictors of hepatocarcinogenesis following eradication of HCV RNA by direct-acting antivirals.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that interferon-based treatment for HCV patients could reduce the risk of hepatocellular carcinoma [17,18,19,20], but that risk factors for hepatocarcinogenesis after elimination of HCV RNA were severe fibrosis, male sex, and older age at the start of interferon treatment [20,21,22,23,24,25]. The present study based on 958 patients with HCV genotype 1 infection is the first to show that severe fibrosis and obesity are important predictors of hepatocarcinogenesis following eradication of HCV RNA by direct-acting antivirals.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reported HCC annual rate after eradication of HCV RNA by antiviral therapy is Յ1% (9,12,13). Based on the results of the present study, we recommend measurement of the core aa70 mutant level of HCV-1b before the start of antiviral therapy for eradication of HCV RNA.…”
mentioning
confidence: 90%
“…P revious reports indicated that amino acid (aa) substitutions at position 70 in the hepatitis C virus (HCV) core region in patients infected with HCV genotype 1b (HCV-1b) are pretreatment predictors of poor virological response to antiviral therapy (1,2) and also affect hepatocarcinogenesis, regardless of treatment response (3-7). In particular, hepatocellular carcinoma (HCC) still occurs even after eradication of HCV RNA by antiviral therapy (8)(9)(10)(11)(12), and substitutions of aa70 at the start of antiviral therapy also affect hepatocarcinogenesis following eradication of HCV RNA (13).…”
mentioning
confidence: 99%
“…For patients with severe fibrosis (F3 or F4) in the liver before treatment (p = 0.007), patients with alcohol intake of greater than 27 g/day (p = 0.015) and patients older than 65 years (p = 0.026), there was a significant independent association of HCC development even if eradication of virus was achieved by effective antiviral therapy [41]. The annual incidence of HCC development in cirrhotic patients with an SVR remained as high as 2.67% per person-year [40].…”
Section: Ifn-based Therapy In Preventing Hcc Developmentmentioning
confidence: 99%